2020
DOI: 10.1177/2292550320925897
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tranexamic Acid in Bimaxillary Orthognathic Surgery

Abstract: Background: Tranexamic acid (TXA) has been widely used during craniofacial and orthognathic surgery (OS). However, results of the literature are inconsistent due to specific type of surgery and a small sample of studies. The purpose of this study was to evaluate the role of TXA in bimaxillary OS. Methods: We performed a comprehensive literature search of PubMed, Cochrane Central Register of Controlled Trials, and EMBASE to identify randomized controlled trials (RCTs) that compared effect of TXA on bimaxillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Only 25% of respondents utilize TXA despite multiple meta-analyses documenting a decrease in blood loss and improvement in surgical field with the use of TXA in orthognathic surgery. [19][20][21][22][23][24] Twenty-seven percent of respondents do not use a foley catheter. The American College of Surgeons National Safety and Quality Improvement Project best practices guidelines for limiting catheter associated urinary tract infections limits perioperative use to selected surgical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 25% of respondents utilize TXA despite multiple meta-analyses documenting a decrease in blood loss and improvement in surgical field with the use of TXA in orthognathic surgery. [19][20][21][22][23][24] Twenty-seven percent of respondents do not use a foley catheter. The American College of Surgeons National Safety and Quality Improvement Project best practices guidelines for limiting catheter associated urinary tract infections limits perioperative use to selected surgical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Only 25% of respondents utilize TXA despite multiple meta-analyses documenting a decrease in blood loss and improvement in surgical field with the use of TXA in orthognathic surgery. 1924…”
Section: Discussionmentioning
confidence: 99%
“…3 Since that time and with increased use, it has been shown to have a beneficial impact on blood loss, rate of transfusion, and length of operations in elective orthopedic, gynecology, cardiac, and neurosurgical procedures. 6,8,[20][21][22][23] This review summarizes the current state of evidence for the use of tranexamic acid in craniofacial and orthognathic surgery. The number of rigorous RCTs which specifically evaluated the use of TXA in craniofacial and orthognathic surgeries are limited and this review identified only 6 studies.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since that time and with increased use, it has been shown to have a beneficial impact on blood loss, rate of transfusion, and length of operations in elective orthopedic, gynecology, cardiac, and neurosurgical procedures. 6,8,20 -23 This review summarizes the current state of evidence for the use of tranexamic acid in craniofacial and orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%